Effect of a Multifactorial Fall Injury Prevention Intervention on Patient Well‐Being: The STRIDE Study. Issue 1 (9th October 2020) - Gill, Thomas M.; Bhasin, Shalender; Reuben, David B.; Latham, Nancy K.; Araujo, Katy; Ganz, David A.; Boult, Chad; Wu, Albert W.; Magaziner, Jay; Alexander, Neil; Wallace, Robert B.; Miller, Michael E.; et al.
Abstract : BACKGROUND/OBJECTIVES: In the Strategies to Reduce Injuries and Develop Confidence in Elders (STRIDE) study, a multifactorial intervention was associated with a nonsignificant 8% reduction in time to first serious fall injury but a significant 10% reduction in time to first self‐reported fall injury relative to enhanced usual care. The effect of the intervention on other outcomes important to patients has not yet been reported. We aimed to evaluate the effect of the intervention on patient well‐being including concern about falling, anxiety, depression, physical function, and disability. DESIGN: Pragmatic cluster‐randomized trial of 5, 451 community‐living persons at high risk for serious fall injuries. SETTING: A total of 86 primary care practices within 10 U.S. healthcare systems. PARTICIPANTS: A random subsample of 743 persons aged 75 and older. MEASUREMENTS: The well‐being measures, assessed at baseline, 12 months, and 24 months, included a modified version of the Fall Efficacy Scale, Patient‐Reported Outcomes Measurement Information System (PROMIS) anxiety and depression scales, and Late‐Life Function and Disability Instrument. RESULTS: Participants in the intervention (n = 384) and control groups (n = 359) were comparable in age: mean (standard deviation) of 81.9 (4.7) versus 81.8 (5.0) years. Mean scores were similar between groups at 12 and 24 months for concern about falling, physical function, and disability, whereas the intervention group's mean scores on anxiety and depression were .7 points lower (i.e., better) at 12 months and .6 to .8 points lower at 24 months. For each of these outcomes, differences between the groups' adjusted least square mean changes from baseline to 12 and 24 months, respectively, were quantitatively small. The overall difference in means between groups over 2 years was statistically significant only for depression, favoring the intervention: −1.19 (99% confidence interval, −2.36 to −.02), with 3.5 points representing a minimally important difference. CONCLUSIONS: STRIDE's multifactorial intervention to reduce fall injuries was not associated with clinically meaningful improvements in patient well‐being.